2022
DOI: 10.1155/2022/3737690
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analysis Model of the Influence of Self‐Efficacy on Professional Toughness of Preschool Teachers under the Condition of Ensuring Children’s Mental Health and Healthy Family Environment

Abstract: Preschool teachers’ professional toughness (PT) has received a lot of attention recently, and this research is one of the main areas of study for their ability to manage stress and develop normally. Based on how well a person thinks of his own abilities, SE (self-efficacy) is formed. 300 kindergarten teachers from 10 metropolitan kindergartens were chosen as research samples in order to examine the relationship between the SE of kindergarten teachers and their PT, as well as the mediating effects of profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%